2000
DOI: 10.3347/kjp.2000.38.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Enterobius vermicularis egg positive rate in a primary school in Chungchongnam-do (Province) in Korea

Abstract: Abstract:The egg positive rate of Enterobius vermicularis was investigated among students of a primary school and a kindergarten located in the rural area of Tangjin-gun, Chungchongnam-do in December, 1998. Of the 189 examinees, 28 (14.8%) were found to be infected with E. vermicularis by the adhesive cellotape anal swab method. The infection rates ranged from 4.2% to 26.1% among school children, and the highest rate was observed in children attending kindergarten. Three months after treatment with albendazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
5
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
3
5
2
Order By: Relevance
“…In the present study, the E. vermicularis infection rate was found to be higher among boys (0.67%, 17/2,537) than in girls (0.55%, 10/1,812), but the difference was not significant ( 2 = 0.399, P = 0.62) ( Table 1). This finding was previously reported worldwide [11][12][13][14]. Preschool children contact each other more frequently in kindergartens and are also exposed to unsatisfactory sanitary environments [15].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, the E. vermicularis infection rate was found to be higher among boys (0.67%, 17/2,537) than in girls (0.55%, 10/1,812), but the difference was not significant ( 2 = 0.399, P = 0.62) ( Table 1). This finding was previously reported worldwide [11][12][13][14]. Preschool children contact each other more frequently in kindergartens and are also exposed to unsatisfactory sanitary environments [15].…”
supporting
confidence: 76%
“…Compared to other countries, our present figure was much lower than that reported in Busan City (8.9%, 13/146) [11], Chungchongnamdo (14.8%, 28/189) [12], and Cheongju City (13.4%, 75/561) [13], Korea, and also in southeastern Estonia (24.4%, 233/954) [14]. In the present study, the E. vermicularis infection rate was found to be higher among boys (0.67%, 17/2,537) than in girls (0.55%, 10/1,812), but the difference was not significant ( 2 = 0.399, P = 0.62) ( Table 1).…”
contrasting
confidence: 54%
“…18.5%) of E. vermicularis infection among children attending kindergartens and primary schools on the western and southern islands of the Republic of Korea. This prevalence is higher than those reported by other workers (7.8-17.5%) since 1991 in the Republic of Korea (Kim et al, 1991;Yang et al, 1997;Lee et al, 2000;Yoon et al, 2000, and is remarkably higher than the national fig It is of note that the detection of E. vermicularis eggs from the peri-anal region means the termination of parasitism by the adult worms that produced these eggs (Akagi, 1973;Cho and Kang, 1975), and that such a finding does not necessarily mean that further worms are present in the intestine. Nevertheless, egg detection from the perianal region is significant, because egg positivity indicates a high probability of infection in the intestine (Cho and Kang, 1975).…”
Section: Discussioncontrasting
confidence: 54%
“…Although a nationwide survey of intestinal parasites showed that the overall E. vermicularis egg positive rate of the Korean population was 0.6%, and that the highest infection rate was found among children in the age range of 5 to 9 years (Ministry of Health and Welfare and Korea Association of Health, 2004). Compared to those reported in previous studies (Yang et al, 1997;Lee et al, 2000;Yoon et al, 2000;Kim et al, 2001;Lee et al, 2001;Kim et al, 2003;Song et al, 2003), which ranged from 9.2 to 26.1%, the total egg positive rate of 248 Korean J. Parasitol. Vol.…”
mentioning
confidence: 78%